Kajian Kualitas Air Sumur Gali Kampung Ujung, Labuan Bajo, Manggarai Barat - Daniel Wolo; Anna S. Rahmawati; Melania Priska (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2020)
This preliminary study aims to determine the quality of shallow water in the area of Kampung Ujung, Komodo District, Labuan Bajo City, West Manggarai Regency in September 2019. Sampling technique using the Purposive Sampling technique that is a determination technique with specific considerations with the number of two-point sampling points. The results of the analysis of physical and chemical testing of shallow water samples from two locations indicate that several parameters are exceeding the Class I Water Quality threshold that it can be a conclusion that the quality of 2 shallow water in Kampung Ujung Labuan Bajo area is not suitable to be used as raw material for water drink.